STUDI PENGARUH WARNA RUANGAN TERHADAP ILLUMINASI LAMPU LED - Adelhard Beni Rehiara (FMIPA Universitas Papua, 2008)
Many previous researches have come to the evidence that LEDs are very efficient in converting electricity to become light. Therefore the question is how background color of a room can influence the illumination of LEDs? Result shows that LEDs illumination is supported by light reflection of the background color. Light from LEDs can be reflected more perfect than neon lamp and glow lamp..